2021
DOI: 10.3389/fphar.2020.591337
|View full text |Cite
|
Sign up to set email alerts
|

Targets of Vitamin C With Therapeutic Potential for Cardiovascular Disease and Underlying Mechanisms: A Study of Network Pharmacology

Abstract: Vitamin C (ascorbic acid) is a nutrient used to treat cardiovascular disease (CVD). However, the pharmacological targets of vitamin C and the mechanisms underlying the therapeutic effects of vitamin C on CVD remain to be elucidated. In this study, we used network pharmacology approach to investigate the pharmacological mechanisms of vitamin C for the treatment of CVD. The core targets, major hubs, enriched biological processes, and key signaling pathways were identified. A protein-protein interaction network a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…More evidence is required to understand the health benefits of this dietary antioxidant, and to potentially curb the rising toll of CVD-related deaths in patients with diabetes or metabolic diseases. This is in support of recent reviews highlighting the gap in clinical evidence informing on the favorable outcomes of vitamin C in individuals at increased CVD-risk ( 27 29 ). Importantly, although other reviews have reported on the potential therapeutic effects of vitamin C on controlling basic metabolic function and CVD-related outcomes ( 26 , 30 , 31 ), very limited information exists on the implications or link with biomarkers of inflammation and oxidative stress such as C-reactive protein (CRP) and interleukin 6 (IL-6), and malondialdehyde (MDA) levels.…”
Section: Introductionsupporting
confidence: 85%
“…More evidence is required to understand the health benefits of this dietary antioxidant, and to potentially curb the rising toll of CVD-related deaths in patients with diabetes or metabolic diseases. This is in support of recent reviews highlighting the gap in clinical evidence informing on the favorable outcomes of vitamin C in individuals at increased CVD-risk ( 27 29 ). Importantly, although other reviews have reported on the potential therapeutic effects of vitamin C on controlling basic metabolic function and CVD-related outcomes ( 26 , 30 , 31 ), very limited information exists on the implications or link with biomarkers of inflammation and oxidative stress such as C-reactive protein (CRP) and interleukin 6 (IL-6), and malondialdehyde (MDA) levels.…”
Section: Introductionsupporting
confidence: 85%
“…Moreover, previous findings evidenced that the risk of CVD is correlated inversely with vitamin C diet supplementation [ 48 , 49 ]. The molecular mechanisms involved in the antioxidant property of AA to prevent and to treat the cardiovascular disorders remain elusive [ 50 , 51 ]. Earlier studies have investigated the signaling pathways involved in the effects of AA on CVD related to periodontal disease [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of thrombosis might be associated with the same pathway as found in cardiovascular diseases. Zhu et al [ 205 ] concluded that the protective role of VC in cardiovascular diseases is related to its anti-inflammatory properties. They suspected that the most enriched pathways of VC are JAK-STAT, PD-1, EGFR, FoxO, and the chemokine-signaling pathways.…”
Section: Vitamin Cmentioning
confidence: 99%
“…Vitamin supplementation during care after ICU discharge might be essential [ 205 ]. After COVID-19, patients are malnourished, and most experience weight loss (about 25%, or more than 8 kg).…”
Section: Vitamin Cmentioning
confidence: 99%